Analysis of Notary Deed as a Basic Reference to Evidence in Civil Law - Sisca Ferawati Burhanuddin (IHSA Institute, 2021)
The law has regulated the making of a civil deed where in the process the authority of a notary in formulating the making of an authentic deed has obtained a legal position in the eyes of the law. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the function of a notary in the role of making an authentic deed can be accounted for based on the Civil Law Act regulated in Article 1868which states that an authentic deed is a deed made in a form determined by law by or before a public official authorized for that at the place where the deed was made. In addition, authentic deed evidence in civil law is said to have perfect and binding evidentiary power which cannot be denied by the judge's proving power in the trial process in court.